2009
DOI: 10.1007/978-3-642-01793-3_56
|View full text |Cite
|
Sign up to set email alerts
|

FM Model Based Fingerprint Reconstruction from Minutiae Template

Abstract: Abstract. Minutiae-based representation is the most widely adopted fingerprint representation scheme. The compactness of minutiae template has created an impression that the minutiae template does not contain sufficient information to allow the reconstruction of the original fingerprint image. This belief has now been shown to be false; several algorithms have been proposed that can reconstruct fingerprint images from minutiae templates. However, these reconstruction techniques have a common weak point: many s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 13 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…The direction of singular points is not used here because it is a redundant feature as long as a few minutiae in the neighborhood of singularity are known, which is almost always the case in our data set. 1 As shown in Fig. 11, the reconstructed orientation field matches the original fingerprint very well, even if the singularity direction is not used.…”
Section: Reconstruction Of Orientation Fieldmentioning
confidence: 84%
See 1 more Smart Citation
“…The direction of singular points is not used here because it is a redundant feature as long as a few minutiae in the neighborhood of singularity are known, which is almost always the case in our data set. 1 As shown in Fig. 11, the reconstructed orientation field matches the original fingerprint very well, even if the singularity direction is not used.…”
Section: Reconstruction Of Orientation Fieldmentioning
confidence: 84%
“…Given a set of N fingerprint minutiae fx n ; y n ; n g, 1 n N, where ðx n ; y n Þ and n denote the location and direction of the nth minutia, respectively, the goal is to reconstruct the original fingerprint image modeled by (1). In terms of the FM model, this input means that we are given 1) the spiral phase and 2) the direction of instantaneous frequency of the composite phase at the locations of the N minutiae.…”
Section: Problem Statementmentioning
confidence: 99%
“…If the security of stored templates is compromised, the attacker can fabricate physical spoof samples to gain unauthorized access. Such efforts have been detailed in [11], [12] and [13]. The stolen templates can also be abused for other unintended purposes, e.g.…”
Section: Need For Template Protectionmentioning
confidence: 99%
“…Recently, several research works showed that this reconstruction is possible. For example, fingerprint can, in fact, be reconstructed from a minutiae template (Cappelli et al, 2007), (Feng & Jain, 2009). …”
Section: Privacy Threats In Biometric Systemsmentioning
confidence: 99%